Analisis Sosiologi Kesehatan Terhadap Perilaku Hidup Sehat Kadet Fakultas Kedokteran Militer Universitas Pertahanan Republik Indonesia - Pannyiwi, Rahmat; Rachman, Arif; Wibowo, Markus (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the healthy lifestyle behaviors of cadets at the Faculty of Military Medicine, the Indonesian Defense University (Unhan RI) through a sociology of health perspective. The background of this study focuses on the importance of a healthy lifestyle for prospective military medical personnel, who play a strategic role in supporting national defense health. The research method used was a qualitative approach with a case study design. Data were obtained through in-depth interviews, observation, and documentation of 30 cadets. The results indicate that cadets' healthy lifestyle behaviors are influenced by internal factors (knowledge, motivation, discipline) and external factors (military education environment, academic culture, and social support). Implementation of healthy lifestyle behaviors includes dietary regulation, regular physical activity, stress management, and adherence to military health regulations. However, barriers such as high academic workloads, limited rest time, and mental stress were also identified. The discussion of this study emphasizes that cadets' healthy lifestyle behaviors are not only the result of individual factors but also a social construct shaped by the military education system. This study suggests the need for strategies to strengthen a healthy lifestyle through educational interventions, psychosocial support, and institutional policies.